Handbook of material weathering - Wypych, George. (ChemTec Pub., 2013)
This book was written to emphasize importance of the material structure in photodegration and photostabilization and also to account for the morphological changes wich occur when materials degrade. This addition makers narrative of material degradation more comprihensive, showing new days to deal with unstable materials.